Pattern of Self-Reported Behavioural Risk Factors of Non-Communicable Diseases among Doctors Working in a Tertiary Care Hospital - Sarkar, Shoman; Dey, Raju; Chowdhury, Bidhan Roy; Ahmed, Shahryar; Chowdhury, Sagar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Behavioural risk factors reduction is a key to Non-Communicable Diseases (NCDs) control. The doctors are educated and aware of society, yet their lifestyle and work habits have led them to suffer from NCDs. This study was carried out to determine the prevalence of the behavioral risk factors of major NCDs among doctors working at Chittagong Medical College Hospital (CMCH). Materials and methods: This cross-sectional study included 145 doctors working at CMCH from April 2020 to September 2020. A structured self-administered questionnaire based on the WHO STEPS instrument for NCDs risks factors surveys was used to collect data. Results: Out of 145 respondents, 104 doctors (71.7%) were males, and 41 doctors (28.3%) were females. Most doctors (50.3%) were aged 23 to 35 years and 29.7% were 35-44 years. The proportion of doctors currently smoking tobacco, drinking alcohol, being sedentary in daily life, and taking low vegetables and fruits was 8.3%, 8.3%, 18.6%, and 72.4%, respectively. No female doctor reported smoking or drinking. Ninety-one (62.8%) of doctors had one risk habit and 17.2% with two risk habits. Conclusion: It is desirable that doctors voluntarily strive to have a favourable lifestyle and that medical institutions actively enlighten doctors’ working at their institutions about this issue. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 14-17